ECOLOGICAL INNOVATION AS A PATHWAY TO A JUST FUTURE: COLLABORATION FOR SHARED PROSPERITY - Zulkarnaen Zulkarnaen; Maulida Ulfa Hidayah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study examines the concept of ecological innovation as a strategy toward a just future through multi-stakeholder collaborative approaches to achieve shared welfare. Using qualitative research methods with a library research approach, this study analyzes the integration of social justice principles in the development and implementation of ecological innovation. Research findings indicate that ecological innovation has evolved from technology-centric approaches to holistic paradigms integrating social, economic, and environmental dimensions. Multistakeholder collaboration involving academia, business, communities, and government proves to be key to success in creating conducive innovation ecosystems. Effective collaborative governance models require the role of intermediaries and catalyst organizations in facilitating knowledge and technology transfer. Implementation in Indonesia shows great potential, particularly in sustainable tourism and responsible digital transformation contexts, but faces structural and institutional challenges such as gender inequality and ineffective coordination. This research recommends policy reformulation that integrates local wisdom and environmental justice, as well as developing comprehensive success indicators to support achieving Sustainable Development Goals through just ecological innovation.